Dissemination of local wisdom and innovation diffusion through routine wirid in Agam, West Sumatra - Zalmi, Fadhila Nurul Husna; Yunita, Rahmi; Rahmi, Lailatur; Fakhlina, Resty Jayanti; Khairunnisa, Syakira; Khairat, Nurul (Universitas Padjadjaran, 2025)
The gap in information accessibility has faded the community's tradition of disseminating knowledge, especially in spreading Islamic teachings. The West Sumatra Provincial Government has revitalized the movement “kembali ka surau” to preserve local traditions in spreading Islamic teachings, including in Agam Regency. Currently, Islamic teachings are still widely conveyed orally in several mosques. Information accessibility is needed to support more effective and sustainable religious learning. In Minangkabau society, information dissemination is fundamental to religious life, with the mosque as its center. This article explored how local wisdom was disseminated through the routine wirid tradition in two main mosques located in Bukittinggi and Ampek Angkek districts of Agam Regency. This study used a qualitative approach with participatory observation, in-depth interviews, and document analysis. Data were collected through direct observation, interviews with religious leaders, and literature reviews from January to March 2024. Findings indicated that wirid effectively disseminated religious values and local wisdom through effective communication channels, consistent scheduling, and an interactive social system. Religious leaders acted as opinion leaders and were reinforced through joint lectures, discussions, and social interactions. Social media enhanced the spread of routine wirid activities. Scheduled routines, reading materials, and technological integration further enriched its impact. This integrated model reveals the powerful potential of routine religious activities as a transformative platform for community education, contextual da'wah, and preservation of local Islamic heritage. In conclusion, the wirid routine in Agam Regency is a medium of da’wah and plays a key role in sustaining, spreading, and preservationg local Islamic wisdom in the local community context.